(397) Iterative Price and Quality Determination for Short Run Productivity ad Foreign Trade Planning تحديد السعر والجودة بشكل متكرر لزيادة الإنتاجية على المدى القصير وتخطيط التجارة الخارجية - Kronsjb, Tom (معهد التخطيط القومى, 2024)
Economic interrelations of importance for short-run production and foreign trade planning may, as a first approximation, be described by a very large linear programming model. The great size of this model necessitates, if it should become managable for practical use. special analysis of its equational structure and exploitation of its special features